The Association Between Comorbidities and a High-Risk Status According to COPD GOLD Groups - Özden Sertçelik, Ümran; Sertçelik, Ahmet; Huseynova, Khurshud; Öncel, Aslı; Damadoğlu, Ebru; Çöplü, Lütfi (Acta Medica, 2022)
Objective: The natural course of the chronic obstructive pulmonary disease (COPD) is thought to be affected by the severity of COPD, frequency of episodes, as well as the presence of comorbid conditions. It was aimed to explore the effect of comorbid conditions on high-risk status in stable COPD patients. Material and methods: Study participants consisted of stable COPD patients attending to the pulmonology outpatient unit of a tertiary center between 15th May 2018 and 12th Dec 2019. Demographic data, comorbidities, clinical index scores, modified Charlson comorbidity index score (mCCI), BODE index score, and the Short Form 36 (SF-36) scores as a generic life quality measure were recorded. Global Initiative for Chronic Obstructive Lung Disease (GOLD) groups were determined based on symptoms and exacerbations. Results: There were 23(25.8%), 31(34.8%), 2(2.2%), and 33(37.1%) patients in GOLD gropus A, B, C, and D, respectively. Among these, A and B groups are considered as low-risk, and C and D groups are considered as high-risk. High risk patients had higher mCCI (p < 0.001) and were more likely to have hypertension (p=0.012), congestive cardiac failure (p=0.029), chronic renal failure (p=0.022), osteoporosis (p=0.001), and anemia (p<0.001). In a logistic regression analysis performed to examine the determinants of high-risk status in COPD-GOLD groups, biomass exposure was found to increase the likelihood of having a high risk-status by 3-fold. Conclusion: Classification of stable COPD patients according to GOLD groups showed higher mCCI in subjects with high-risk status. Comorbidities and mCCI did not appear to affect the high-risk status. Biomass exposure was associated with an increased risk of having a high-risk status.